Effect of Moringa oleifera leaf powder supplementation on acute respiratory infection in children aged 36–59 months: a quasi-experimental study - Nurhi Kefi Nomenci Babu; Fitriyono Ayustaningwarno; Nuryanto; Nur Afifah , Diana (MEDISAINS: Jurnal Ilmiah Ilmu-Ilmu Kesehatan, 2026)
Background: Acute Respiratory Infection (ARI) remains a leading cause of morbidity and mortality among children under five, particularly in settings with poor nutritional status and sanitation. Moringa oleifera has been recognized for its nutritional and immunomodulatory properties; however, evidence regarding its effect on ARI incidence in undernourished children is still limited. Objective: This study aimed to examine the effect of Moringa oleifera leaf powder supplementation on the incidence of ARI among children aged 36–59 months. Methods: A quasi-experimental study with a pretest–posttest control group design was conducted from May to July 2025 at Batuputih Public Health Center, South Central Timor District, Indonesia. A total of 40 children were equally allocated into intervention and control groups. The intervention group received 15 g/day of moringa leaf powder combined with eggs, vitamin C, and B complex for 60 days, while the control group received the same supplementation without moringa. ARI incidence was assessed based on clinical diagnosis and hematological parameters, including leukocyte, lymphocyte, and monocyte counts. Data were analyzed using appropriate non-parametric and parametric tests, with statistical significance set at p < 0.05. Results: The intervention group showed a greater reduction in ARI incidence compared with the control group (from 20 to 3 children vs. 20 to 9 children; p = 0.038). Significant changes were also observed in leukocyte levels following supplementation (p = 0.007). Conclusion: Moringa oleifera leaf powder supplementation was associated with a reduction in ARI incidence among children aged 36–59 months and may serve as a potential supportive nutritional intervention in high-risk populations.